Construction of Isomorphous Coordination Polymers with 2‐(3‐(pyridin‐2‐yl)‐1H‐pyrazol‐1‐yl) acetate Ligand: Structures, Fluorescent Temperature Sensing, and Magnetic Properties. Issue 17 (21st April 2021) - Shen, Chenhu; Xie, Yibing; Kong, Bingshan; Ma, Jing‐xin; Yang, Jinhui
Abstract: In this work, four isomorphous two‐dimensional (2D) complexes, [M(PPA)(HCOO)]n (M=Zn (1 ), Co (2 ), Ni (3 ) and Cd (4 )) have been synthesized under solvothermal conditions by mixed 2‐(3‐(pyridin‐2‐yl)‐1H‐pyrazol‐1‐yl) acetate (PPA) with transition metal ion (Zn 2+, Co 2 +, Ni 2+ or Cd 2+ ). Single‐crystal and powder X‐ray diffraction show that the four complexes are isomorphous. Due to different electronic configurations for Zn 2+, Co 2+, Ni 2+, and Cd 2+, the solid‐state fluorescence properties of 1 and 4, and the temperature dependence of magnetic susceptibility of 2 and 3 were investigated, respectively. The results show that 1 and 4 have obvious blue light emission at the range of 310 to 430 nm with 1.37 % of the quantum yield and 3.80 ns of the lifetime for 1 and 1.67 % and 2.43 ns for 4, respectively. Notably, the intensity‐based fluorescent temperature sensing reveals that both of them can be used as luminescent thermometers. Magnetic investigation of 2 and 3 reveals that strong antiferromagnetic interactions exist within the paramagnetic centers, Co(II) or Ni(II), with −29.09 K of Weiss constant for 2 and −64.02 K for 3, respectively. Abstract : By reacting 2‐(3‐(pyridin‐2‐yl)‐1H‐pyrazol‐1‐yl) acetate (PPA) with transition metal ions, four new isostructural 2D coordination polymers, [M(PPA)(HCOO)]n (M=Zn (1 ), Co (2 ), Ni (3 ) and Cd (4 )), were assembled under solvothermal conditions. The study showed that 1 and 4 could be used as luminescent thermometers, while there was strong antiferromagnetic interaction in 2 and 3 with −29.09 K and −64.02 K of Weiss constant.